Calcium Calmodulin-Stimulated Adenylyl Cyclases Contribute to Activation of Extracellular Signal-Regulated Kinase in Spinal Dorsal Horn Neurons in Adult Rats and Mice - Wei, Feng (J Neurosci, 2006)
The extracellular signal-regulated kinase (Erk) cascades are suggested to contribute to excitatory synaptic plasticity in the CNS, including the spinal cord dorsal horn. However, many of their upstream signaling pathways remain to be investigated. Here, we demonstrate that glutamate and substance P (SP), two principal mediators of sensory information between primary afferent fibers and the spinal cord, activate Erk in dorsal horn neurons of both adult rat and mouse spinal cord. In genetic knock-out mice of calcium calmodulin-stimulated adenylyl cyclase subtypes 1 (AC1) and 8 (AC8), activation of Erk in dorsal horn neurons were significantly reduced or blocked, either after peripheral tissue inflammation or by glutamate or SP in spinal cord slices. Our studies suggest that AC1 and AC8 act upstream from Erk activation in spinal dorsal horn neurons and the calcium-AC1/AC8-dependent Erk signaling pathways may contribute to spinal sensitization, an underlying mechanism for the development of persistent pain after injury.